Tani Segar / Mohd Nazharafis Mokhtar ... [et al.] - Mokhtar, Mohd Nazharafis; Abdul Rahman, Zamri; Hamat, Abdul Jalil; Mohd Noh, Mohd Kamarul; Yussoff, Mohd Zubairi (Faculty of Civil Engineering, 2006)
TANI SEGAR is run by five partners which is 100% own by Bumiputera. All partners are agreed to choose TANI SEGAR' as our business's name. We choose 'SEGAR1 from Malay's word which means fresh. TANI SEGAR is a partnership type of business. We have chosen partnership because there are a lot of ideas, talents, and skills can be pooled together for better management. The responsibility of managing and handling the business can be divided equally among partners. Besides that, business risks can be reduced and distributed among partners.